A Study of Quantitative, Qualitative, and Mixed Methods Data Analysis Techniques in Indonesian National Journal Articles: Systematic Literature Review - Muhammad Raihan As Syauqi; Bayu Bambang Nurfauji; Harkat Hadi Saputra; Yohanna Zuriyah; Tedi Priatna (Penerbit Hellow Pustaka, 2026)
Data analysis techniques play a crucial role in scientific research as they determine the validity and quality of research findings. Recent developments in Indonesian research indicate an increasing diversity in the use of quantitative, qualitative, and mixed data analysis techniques. Therefore, a comprehensive review is required to systematically examine these developments. This study aims to analyze quantitative and qualitative data analysis techniques used in Indonesian national journal articles. The research employs a Systematic Literature Review (SLR) method by examining national journal articles published in Indonesia from 2021 to 2025. The SLR process was conducted through several stages, including the formulation of research questions, systematic literature searching, article selection based on inclusion and exclusion criteria, and data synthesis and analysis. The results indicate that quantitative data analysis techniques remain dominant, particularly descriptive statistics, regression analysis, correlation analysis, and analysis of variance. Meanwhile, qualitative data analysis techniques such as thematic analysis, narrative analysis, and content analysis are widely used to obtain an in-depth understanding of research phenomena. In addition, the use of mixed methods approaches has shown a growing trend, as they provide more comprehensive and robust research findings. This study is expected to serve as a methodological reference for researchers in selecting appropriate data analysis techniques based on research objectives and data characteristics.